The Implementation of Inclusion in Corruption Case Handling - Syachdin Syachdin (Universitas Lampung, 2018)
The formulation of problem in the implementation of inclusion in handling corruption case has reflected the legal objectives which are legal certainty, justice, and expediency, and inconsistency in implementing the inclusion in handling corruption case, the purpose of the research is To find out and analyze the application of inclusion in handling corruption case has reflected the legal purposes which are legal certainty, justice and expediency and To find out and analyze the inconsistency in applying of inclusion in handling of corruption case, using empirical research method which resulted that there is indication that the implementation of inclusion is not yet implemented which causing inconsistency of law enforcement officer, i.e., Police, Attorney in applying the article of inclusion in handling of case corruption and inconsistency in the application of inclusion in corruption cases causes the occurrence of discrimination in the process of law enforcement, so that does not reflect the legal purpose of legal certainty. It is recommended that to create legal objectives, law enforcement officers must be consistent in applying the articles of inclusion in the handling of corruption cases and to achieve legal certainty should investigators, and prosecutors apply the juridical participation in corruption cases. Keywords: Implementation, Inclusion, Corruption Case